Three new false spider mites of the genus Pseudoleptus Bruyant (Acari: Tenuipalpidae) from Iran - Khanjani, Masoumeh; Khanjani, Mohammad; Saboori, Alireza; Seeman, Owen D. (Zootaxa, 2012)
Three new species of Pseudoleptus are described from Iran: P. hamedaniensis sp. nov. from Bromus tectorum (Poaceae),P. iranensis sp. nov. from Bromus danthoniae (Poaceae), and P. kermanshahiensis sp. nov. from Alopecurus myosuroides(Poaceae). The genus Pseudoleptus is rediagnosed and its relationship with the Aegyptobia macswaini species group discussed. A key to all known species of this genus is given.